Traveling and abrasion characteristics of wheels for lunar exploration rover in vacuum. (December 2016) - Sutoh, Masataku; Wakabayashi, Sachiko; Hoshino, Takeshi
Highlights: A traveling test system that enables a wheel to continuously travel was developed. Traveling performances of wheels were investigated at various pressure levels. Abrasion of a wheel was evaluated at various intervals of a traveling distance. The findings obtained for vacuum provide guidelines for wheels of lunar rovers. Abstract: This paper investigates the traveling and abrasion characteristics of rigid wheels for a lunar exploration rover at atmospheric pressure and in a vacuum. For this investigation, a traveling test system that enables the wheel to continuously travel over a long distance was developed. Using this system, tests on traveling performance and abrasion were conducted with the wheel on a lunar regolith simulant surface. In the initial tests, various wheels traveled over different ground conditions and their performances were evaluated based on the relationship between the drawbar pull and slippage. In the later tests, a wheel with grousers traveled a distance of 3 km and the abrasion was analyzed at various intervals. From the traveling performance tests, it was found that for a soft ground condition, the traveling performance of the wheels in vacuum was slightly lower than that in atmosphere. This indicates that ground tests performed in atmosphere overestimate the actual performance on the lunar surface. The abrasion tests suggested that the scratching of wheels occurs more easily in vacuum than in atmosphere. These experiments confirmed that the abrasion of the wheels do not cause any critical problem for a traveling distance of up to 3 km in a simulated lunar environment.